Silencing of a Germin-Like Gene in Nicotiana attenuata Improves Performance of Native Herbivores - Lou, Yonggen (American Society of Plant Biologists, 2006)
Germins and germin-like proteins (GLPs) are known to function in pathogen resistance, but their involvement in defense against insect herbivores is poorly understood. In the native tobacco Nicotiana attenuata, attack from the specialist herbivore Manduca sexta or elicitation by adding larval oral secretions (OS) to wounds up-regulates transcripts of a GLP. To understand the function of this gene, which occurs as a single copy, we cloned the full-length NaGLP and silenced its expression in N. attenuata by expressing a 250-bp fragment in an antisense orientation with an Agrobacterium-based transformation system and by virus-induced gene silencing (VIGS). Homozygous lines harboring a single insert and VIGS plants had significantly reduced constitutive (measured in roots) and elicited NaGLP transcript levels (in leaves). Silencing NaGLP improved M. sexta larval performance and Tupiocoris notatus preference, two native herbivores of N. attenuata. Silencing NaGLP also attenuated the OS-induced hydrogen peroxide (H(2)O(2)), diterpene glycosides, and trypsin proteinase inhibitor responses, which may explain the observed susceptibility of antisense or VIGS plants to herbivore attack and increased nicotine contents, but did not influence the OS-elicited jasmonate and salicylate bursts, or the release of the volatile organic compounds (limonene, cis-α-bergamotene, and germacrene-A) that function as an indirect defense. This suggests that NaGLP is involved in H(2)O(2) production and might also be related to ethylene production and/or perception, which in turn influences the defense responses of N. attenuata via H(2)O(2) and ethylene-signaling pathways.